Hubungan Antara Kekuatan Otot Lengan Dengan Kemampuan Lemparan Ke Dalam Pada Permainan Sepak Bola Mahasiswa Program Studi Pendidikan Jasmani Kesehatan Dan Rekreasi (PJKR) - Anggi Septiandreas Sinaga (STIKES Columbia Asia Medan, 2025)
This study aims to determine the relationship between arm muscle strength and the ability to perform a throw-in in football among sixth-semester students of the Physical Education, Health, and Recreation Study Program (PJKR) at Manado State University. The throw-in technique is one of the basic skills in football, used to return the ball into play with both hands from behind and over the head. An effective throw-in requires optimal arm muscle strength. This research employed a quantitative correlational approach, involving a sample of 20 randomly selected students. The instrument used to measure arm muscle strength was a one-minute push-up test, while throw-in ability was measured by the distance of the throw in meters. Hypothesis testing was conducted using the Pearson Product Moment correlation test with a significance level of α = 0.05. The results of the analysis indicated a significant relationship between arm muscle strength and throw-in ability in football. These findings highlight the importance of arm strength training in developing fundamental football techniques, particularly the throw-in.